CFD modelling of a mixing chamber for the realisation of functionally graded scaffolds. (4th January 2016) - Mattei, G.; Vozzi, G.
Highlights: We model hydroxyapatite particle mixing within a gelatin solution in a stirred tank. The stirred tank geometry and configuration allow to obtain homogeneous suspensions. Discrete or continuous graded bone scaffolds can be obtained from these suspensions. Results help to design small stirred tanks for automated bone scaffold fabrication. Abstract: Biological tissues are characterised by spatially distributed gradients, intricately linked with functions. It is widely accepted that ideal tissue engineered scaffolds should exhibit similar functional gradients to promote successful tissue regeneration. Focusing on bone, in previous work we proposed simple methods to obtain osteochondral functionally graded scaffolds (FGSs), starting from homogeneous suspensions of hydroxyapatite (HA) particles in gelatin solutions. With the main aim of developing an automated device to fabricate FGSs, this work is focused on designing a stirred tank to obtain homogeneous HA–gelatin suspensions. The HA particles transport within the gelatin solution was investigated through computational fluid dynamics (CFD) modelling. First, the steady-state flow field was solved for the continuous phase only. Then, it was used as a starting point for solving the multi-phase transient simulation. CFD results showed that the proposed tank geometry and setup allow for obtaining a homogeneous suspension of HA micro-particles within the gelatin solution.